2019
DOI: 10.2185/jrm.2993
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Gd-EOB-DTPA-enhanced MRI for evaluating the potential for early development of hepatocellular carcinoma after HCV eradication by direct-acting antiviral treatment

Abstract: Objective: The development of hepatocellular carcinoma (HCC) is not uncommon in patients who achieve eradication of the hepatitis C virus through direct-acting antiviral (DAA) treatment. The aim of this study was to identify the patients at high risk for novel HCC development after a sustained virologic response (SVR) by DAA treatment. Patients and Methods: A total of 518 patients with no history of HCC treatment and who achieved SVR by DAA treatment were evaluated retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Mariño Z, et al (28) reported the presence of non-characterized nodules before DAA was associated with a 3 times greater risk of HCC development. Therefore, screening of the early stage of HCC by other imaging modalities such as EOB-MRI before therapy could reduce the incidence of HCC after SVR since no lesions were detected by the US alone at baseline in our study and EOB-MRI is superior to detecting early HCC (29,30).…”
Section: Discussionmentioning
confidence: 72%
“…Mariño Z, et al (28) reported the presence of non-characterized nodules before DAA was associated with a 3 times greater risk of HCC development. Therefore, screening of the early stage of HCC by other imaging modalities such as EOB-MRI before therapy could reduce the incidence of HCC after SVR since no lesions were detected by the US alone at baseline in our study and EOB-MRI is superior to detecting early HCC (29,30).…”
Section: Discussionmentioning
confidence: 72%
“…A novel HCV fibrosis marker called M2BPGi has recently been described as a predictor of the development of HCC following SVR 64,120,121 . M2BPGi has been tested in HCC occurrence after SVR; however, in this cohort, In the multivariate study, M2BPGi was not a significant factor, although it might indicate additional factors, such as liver inflammation as it increases after acute liver injury 122 …”
Section: Risk Factors Of Hcc Development After Svrmentioning
confidence: 89%
“…While prior studies have tried to identify demographic and clinical predictors of HCC development in patients treated with DAA, 11,12,31,32 scant data exist regarding the role of indeterminate lesions on the risk of de novo HCC. These data were limited by heterogeneous definition of indeterminate liver nodules and lack of information about the outcome of indeterminate nodules itself 33‐36 . Mariño et al 33 reported an increased relative risk of de novo HCC in cirrhotic patients with indeterminate liver nodules at ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ooka et al 34 reported the presence of “dysplastic nodules” detected at CT or MRI as the only significant feature independently associated with HCC occurrence at 1‐year after DAA. Morimoto et al 35 described non‐hypervascular hypointense nodules on MRI as the only factor correlated with subsequent HCC development after DAA, while Toyoda et al 36 analysed the incidence of hypervascularization in non‐hypervascular hypointense nodules on gadoxetate disodium‐MRI demonstrating no difference in the development of arterial phase hyperenhancement in patient with eradicated HCV, compared to patient with persistent HCV infection. In clinical practice, indeterminate liver nodules may carry a higher risk of malignancy progression according to the combination of specific imaging features 19,37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation